Social Practices of Young People in The Moscow Region Associated with The Spread of The Covid-19 Pandemic - Yuryevna Kirilina, Tatiana (2021)
The COVID-19 pandemic has spread rapidly around the world and has had significant impact on changing the social practices of everyday behavior and interpersonal communication of people. In Russia, the Moscow Region was one of the leaders in the number of people infected with COVID-19. Therefore, the focus of the present study is on the everyday social practices of students in the Moscow Region during the COVID-19 pandemic, as well as the attitude of young people to restrictions and measures aimed at countering the spread of coronavirus infection in the region. The findings of the study are based on the results of a questionnaire survey of more than 2,500 young respondents studying at universities, colleges, and technical schools in the Moscow Region, conducted during the second wave of the pandemic. The conducted analysis has shown that more than half of the respondents admitted that they were afraid of contracting coronavirus and considered it a very dangerous disease. Nevertheless, young people's adherence to safety standards was often due to the strict requirements of the authorities and the public to comply with them. The most common measures taken by respondents to prevent COVID-19 included frequent handwashing with soap, wearing face masks in public places, wiping hands with antiseptic, and avoiding contact with sick people.